STRATEGI PEMASARAN SYARI’AH KEDAI TERMINAL BAMBU KRAKSAAN - Yeni Fatur Rohmah; Santi Rahmawati (IZZI: Jurnal Ekonomi Islam, 2022)
Marketing strategy is a set of goals and objectives, policies and rules that provide direction to marketing efforts over time, Strategy is the overall concept of how a company regulates itself and all activities with the aim of making the business run successfully, competitive, and generate returns to shareholders, Islamic marketing is a strategic business discipline that directs the process of creating, offering, and changing values ​​from one initiator to its stakeholders. This study aims to determine the sharia marketing strategy of the case study of the kraksaan bamboo terminal shop. This research method uses descriptive qualitative research methods and uses case study research. one form of real adaptation that has been implemented as well as empowering its potential for the benefit of the environment. From the research above, we can conclude that the sharia marketing strategy at the kraksaan bamboo terminal shop is to carry out its business activities professionally.